Platforms, profits and PISA for schools: new actors, by-passes and topological spaces in global educational governance. Issue 1 (2nd January 2023) - Lewis, Steven; Lingard, Bob
ABSTRACT: This paper focuses on the Organisation for Economic Cooperation and Development's (OECD) PISA for Schools assessment. Our first substantive focus is a descriptive and analytical account of changes and developments in the functioning of this ground-breaking assessment since its creation in 2012. These changes include an expansion of the number and diversity of participating schools and countries, the introduction of a 'user-pays' model, the enhanced role of edtech firms and an explicit capacity-building focus, which we argue helps to strengthen an instrument constituency for the broader OECD testing regime. The second focus of the paper is the impact of PISA for Schools on changing modes of educational governance, situated against emerging spatialities of globalisation. Here, we provide an analysis using the concept of 'by-passes', which we elaborate as spatial, governance and systemic, to understand the new topological spatialities of globalisation and the global governance effects of these specific by-passes.